Penerapan Good Environmental Governance Pada Program Tempat Olah Sampah Setempat (TOSS) Sebagai Inovasi Pelayanan Publik Di Kabupaten Klungkung (Studi Kasus: TOSS Center Gema Santi Karangdadi) - Pinatih, Dewa Ayu Agung Intan; Yasintha, Putu Nomy; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2022)
Klungkung Regency, as one of the regencies located in Bali Province, tries to implement Good Environmental Governance through public service innovations in the form of the Local Waste Processing Place Program or TOSS Center Gema Santhi Karangdadi to overcome waste problems and their management, especially for urban areas. TOSS itself still has various problems, both in terms of environmental governance and innovation in public services. This study uses a descriptive-exploratory method with purposive and snowball sampling techniques. The results show that the TOSS Center Gema Santhi Karangdadi program in Klungkung Regency in terms of Good Environmental Governance and public service innovation is still not fully optimized. However, TOSS Center needs to improve several things, especially on community participation, transparation, human resources and facilities infrastructure. Keywords: TOSS Center Gema Santhi, Klungkung Regency, Good Environmental Governance, Public Service Innovation